A study of optimum coconut shell (CS) ratio in cement sand bricks - Noorhaya, Kasa (2015)
This thesis is an overview a study of optimum ratio of coconut shell cement sand brick (CSCSB). Cement is used as the binding material for coconut shell and sand. In this study, a standard mix used is cement: sand, which is ratio 1: 6, a coconut shells are added by using difference ratio. The mix proportions of CSCSB are cement: sand: coconut shells, ratios used are 1: 5: 1, 1: 4.5: 1.5 and 1: 3: 3. There are total of 90 CSCSB was produced in this research, with dimension of 225 mm x 113 mm x 75 mm. Air curing is selected, since CSCSB is a sensitive brick. The properties of CSCSB will be define by undergo necessary testing such as compression test at 3, 7, 14 and 28 days, density test and water absorption rate test. The value of compressive strength of CSCSB is decreasing as the ratio of coconut shell is increases. Even though a compaction is done properly during brick casting, since coconut shell are irregular shape, the void or porous space may produce during brick casting, this void or porous space may lead to a strength reduction. The density of CSCSB is decreased with increase in coconut shell. This decreased density is due to the fibrous nature of the coconut shell, where coconut shell has a low density. The water absorption rate is increased with increased of coconut shells. The water absorption rate is increase due to the porous space of CSCSB, where is water can get through the porous area in brick, since coconut shell is fibrous, thus make it easier to absorb water. From this study, the optimum ratios are obtained, where ratio 1:4.5:1.5 shows the best performance which satisfied with the standard control. The use of coconut shell in cement sand brick is an alternative to encourage environmental protection in order to minimize waste material.